Analisis Gaya Kepemimpinan Kepala Sekolah dan Dampaknya terhadap Manajemen Sekolah di SMKS 2 Taman Siswa Pematang Siantar - Ratnasari, Ratnasari; Sulasmi, Emilda (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2025)
Principals are central to educational leaders who have a policy to be able to lead a school to achieve predetermined goals. The results of the study, the principal's style at SMKS 2 Tamansiswa Pematangsiantar in leading his school uses a positive leadership style, namely democratic. For the implementation of school management at SMKS 2 Tamansiswa Pematangsiantar obtained an average presentation of 86%, meaning that it has a high interpretation with a good category. This shows that SMKS 2 Tamansiswa Pematangsiantar has carried out management functions well. The contribution given by the principal's leadership style (X) to school management (Y) is 0.733 including in the strong category, so there is a strong and positive influence between the principal's leadership style on school management at SMKS 2 Tamansiswa Pematangsiantar.